2019
DOI: 10.1002/mrd.23297
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation stability in fish spermatozoa upon external constraint: Impact of fish hormonal stimulation and sperm cryopreservation

Abstract: Highly differentiated mature spermatozoa carry not only genetic but also epigenetic information that is to be transmitted to the embryo. DNA methylation is one epigenetic actor associated with sperm nucleus compaction, gene silencing, and prepatterning of embryonic gene expression. Therefore, the stability of this mark toward reproductive biotechnologies is a major issue in animal production. The present work explored the impact of hormonal induction of spermiation and sperm cryopreservation in two cyprinids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…Recently, other studies have revealed the effects of cryopreservation on sperm DNA methylation, which is a major epigenetic modification and plays a crucial role in sperm nucleus compaction, gene silencing and prepatterning of embryonic gene expression [ 41 ]. For goldfish ( Carassius auratus ) sperm, global DNA methylation was not affected after cryopreservation with methanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other studies have revealed the effects of cryopreservation on sperm DNA methylation, which is a major epigenetic modification and plays a crucial role in sperm nucleus compaction, gene silencing and prepatterning of embryonic gene expression [ 41 ]. For goldfish ( Carassius auratus ) sperm, global DNA methylation was not affected after cryopreservation with methanol.…”
Section: Discussionmentioning
confidence: 99%
“…For goldfish ( Carassius auratus ) sperm, global DNA methylation was not affected after cryopreservation with methanol. In contrast, cryopreservation with methanol induced a slight, but significant, increase in global DNA methylation of zebrafish ( Danio rerio ) sperm [ 41 ]. In addition, cryoprotectant could alter the pattern of sperm DNA methylation of tambaqui ( Colossoma macropomum ), decreasing the global methylation level [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, while histones are extensively reprogrammed early in development (Labbé et al, 2017;Zhu et al, 2019), parental contributions might be highly context dependent (e.g. particular mark, species and/or environment; Depincé et al, 2020;Larose et al, 2019;Loppin & Berger, 2020;Tabuchi et al, 2018), and parental imprinting in fish gametes has still not been conclusively shown (Labbé et al, 2017). Our study, thus, highlights the variation among species and need for more studies in non-model organisms to allow generalizations and unifying principles of epigenetic reprogramming to be identified (Ortega-Recalde & Hore, 2019).…”
Section: Epigenetic Reprogramming Dynamics In Sticklebackmentioning
confidence: 99%
“…Specifically, differential expression of Brdt and piwil1 in testes after 6 weeks acclimation at 21°C suggests that warming may have an influence on the spermatogenesis process (Alix et al, 2020), shaping final sperm chromatin conformation (SNPBs, remaining histones and chromatin accessibility differences) and sperm-specific transcript accumulation (SSTA;Ben Maamar et al, 2020;Eirin-Lopez & Ausio, 2009;Labbé et al, 2017;Raz, 2003;Robles et al, 2017). However, consequences for replacement of somatic histones by SNBPs, chromatin conformation and SSTA may be species-and environment-specific (Depincé et al, 2020), and remain to be elucidated. In ovaries, temperature increase might have consequences for oogenesis through 5hmC (Fu et al, 2017), and on maternal mRNA provisioning of chromatin-modifying enzymes and histone variants necessary in mature oocytes for development (Xia & Xie, 2020;Xu, 2021).…”
Section: Temperature-sensitive Reprogramming At Key Windows During Developmentmentioning
confidence: 99%
See 1 more Smart Citation